2021
DOI: 10.18494/sam.2021.3314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excitation Density on the Scintillation Properties of Organic–Inorganic Layered Perovskite-type Compounds

Abstract: The scintillation properties of organic-inorganic layered perovskite-type compounds were analyzed using pulsed beams having different linear energy transfers (LETs). Initially the decay was slower and then became faster at higher LETs. A possible cause of the slower decay at higher LETs is the competition between the radiative process and trapping at nonradiative sites, resulting in some excitons not being trapped at nonradiative sites at which other excitons have already been trapped at higher LETs. The faste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Excitons confined in the inorganic layers have a high binding energy, and thus fast and highly efficient luminescence can be expected. (18,19) As further advantages, the perovskite crystals can be grown at a low cost owing to a low-temperature process in comparison with most inorganic scintillators synthesized by melt-growth methods (e.g., Czochralski, Bridgeman, and Floating Zone methods). (6,(20)(21)(22) According to a previous study, (C 6 H 5 C 2 H 4 NH 3 ) 2 PbBr 4 has shown high LY (14000 ph/MeV) and fast scintillation decay time (11 ns).…”
Section: Introductionmentioning
confidence: 99%
“…Excitons confined in the inorganic layers have a high binding energy, and thus fast and highly efficient luminescence can be expected. (18,19) As further advantages, the perovskite crystals can be grown at a low cost owing to a low-temperature process in comparison with most inorganic scintillators synthesized by melt-growth methods (e.g., Czochralski, Bridgeman, and Floating Zone methods). (6,(20)(21)(22) According to a previous study, (C 6 H 5 C 2 H 4 NH 3 ) 2 PbBr 4 has shown high LY (14000 ph/MeV) and fast scintillation decay time (11 ns).…”
Section: Introductionmentioning
confidence: 99%
“…(3) In general, an X-or γ-ray scintillator requires a high scintillation light yield (LY), short decay time, high energy resolution, high density, large effective atomic number, and low afterglow. Therefore, there has been continuous R&D to develop more desirable materials in single crystal, (4)(5)(6)(7)(8)(9)(10)(11)(12) ceramic, (13)(14)(15) glass, (16)(17)(18)(19) and liquid forms. (20)(21)(22) A high density and a large effective atomic number are important for obtaining large cross sections against X-and γ-rays; (23) thus, pyrochlore rare-earth hafnates (RE 2 Hf 2 O 7 , RE: rare earth) are potential scintillators with high density (9.0 and 9.7 g/cm 3 for Gd 2 Hf 2 O 7 and Lu 2 Hf 2 O 7 , respectively (24) ) and large effective atomic numbers (66-69).…”
Section: Introductionmentioning
confidence: 99%
“…For several decades until now, solid-state scintillators in various forms of materials, including plastics, (5) glasses, (6)(7)(8)(9)(10) single crystals, (11)(12)(13)(14)(15)(16) transparent ceramics, (17)(18)(19)(20) and composite materials, have been developed. (21,22) Among all the possible materials, single crystals are one of the promising choices because the single-crystal scintillator has many advantages, including high chemical stability, transparency, and high scintillation light yield. An obvious disadvantage is the typically higher cost to produce single crystals.…”
Section: Introductionmentioning
confidence: 99%